2015
DOI: 10.9738/intsurg-d-15-00118.1
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue Inhibits the Inflammatory Process of the Acetic Acid-Induced Colitis in Rat Colonic Mucosa

Abstract: Inflammatory bowel disease is a serious health problem. Although it has been widely investigated, treatment of inflammatory bowel diseases currently remains as a challenging clinical problem. Over production of nitric oxide has been demonstrated to cause tissue damage and inflammation. In this study, the effect of methylene blue (MB), a well-known inhibitor of nitric oxide synthesis, was investigated in acetic acid (AA)-induced colitis model in Sprague-Dawley rats. Eighty male rats randomized into 4 groups (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…No systematic studies have been conducted to evaluate possible negative effect of MB on the gastrointestinal tract. In contrast, MB was found to demonstrate the therapeutic effect against ulcerative colitis induced by intrarectal administration of 2,4,6-trinitrobenzene sulfonic acid [31] and against acetic acid-induced colitis in colonic mucosa [32]. However, a single case was reported when a standard procedure of submucosal injection of 0.01% MB during colon resection induced acute localized colitis [33].…”
Section: Discussionmentioning
confidence: 97%
“…No systematic studies have been conducted to evaluate possible negative effect of MB on the gastrointestinal tract. In contrast, MB was found to demonstrate the therapeutic effect against ulcerative colitis induced by intrarectal administration of 2,4,6-trinitrobenzene sulfonic acid [31] and against acetic acid-induced colitis in colonic mucosa [32]. However, a single case was reported when a standard procedure of submucosal injection of 0.01% MB during colon resection induced acute localized colitis [33].…”
Section: Discussionmentioning
confidence: 97%
“…Dinç et al [11] used MB in rats in an experimental colitis model induced with acetic acid, and observed antioxidant effect of MB by reducing the harmful effects of NO and anti-inflammatory effect by suppressing TNF-α, IL-1 beta (β), and IL-6 levels. Privistirescu et al [24] reported that MB applied to rats with diabetes mellitus had an antioxidative effect in alleviating endothelial dysfunction and reducing endothelial oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Recent studies have shown that MB decreases the levels of inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1, and IL-6 and shows anti-inflammatory and antioxidant effects as well as reducing the harmful effects of nitric oxide (NO). [ 11 ] It is thought that MB will both accelerate the tendon healing process and reduce the adhesion that may occur in the postoperative period, particularly with its anti-inflammatory, antioxidant and antimicrobial effect. [ 10 , 11 ] To the best of our knowledge, there is no study in the literature investigating the effect of MB on flexor tendon healing.…”
Section: Introductionmentioning
confidence: 99%
“…MB displays diverse biological activities, including memory-enhancing, antioxidant, anti-inflammatory, and anti-tumor effects [ 17 19 , 34 ]. Its strong lipophilic property make it rapidly cross the blood-brain barrier and easily accumulate in the brain tissue to exert a direct neuroprotective effect [ 20 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methylene blue (MB) is a water-soluble thiophenazine compound widely used in clinical treatment of multitudinous diseases. Previous studies have demonstrated that MB exerts diverse pharmacological effects such as anti-inflammatory, antioxidant, and anti-apoptosis effects [ 17 19 ]. Therefore, in recent years, the role of MB in the treatment of various central nervous system diseases has generated widespread interest.…”
Section: Introductionmentioning
confidence: 99%